AIDS-related deaths in Turkey between 2009 and 2018 - Teker, Ayse Gulsen (My University, 2021)
Abstract The prevalence of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is increasing day by day in the region, including Turkey. The study aimed to examine AIDS-related deaths in Turkey between 2009 and 2018 according to the national death registration system records. In this descriptive study, data on AIDS-related deaths were obtained from the Turkish Statistical Institute. The data consist of the cause of death codes, year of death, age and gender. Findings were presented using numbers and percentages. Seven hundred twenty-one AIDS-related deaths were reported in Turkey between 2009 and 2018. AIDS-related deaths in Turkey increased more than twice at the end of 10 years. The male/female death ratio is 4.5. Deaths under the age of 15 were 4.2% in total; however, they were increased to 10.2% in 2018. AIDS-related deaths are decreasing in the world but increasing in Turkey. The data from the Ministry of Health do not match the data of the national death registration system. Establishing a strong and accurate HIV/AIDS reporting system and identifying the causes and risk groups of this increase in AIDS-related deaths are critical.